Charcot-Marie-Tooth 2b associated Rab7 mutations cause axon growth and guidance defects during vertebrate sensory neuron development. Issue 1 (December 2016) - Ponomareva, Olga; Eliceiri, Kevin; Halloran, Mary
Abstract Background Charcot-Marie-Tooth2b (CMT2b) is an axonal form of a human neurodegenerative disease that preferentially affects sensory neurons. CMT2b is dominantly inherited and is characterized by unusually early onset, presenting in the second or third decade of life. Five missense mutations in the gene encoding Rab7 GTPase have been identified as causative in human CMT2b disease. Although several studies have modeled CMT2b disease in cultured neurons and inDrosophila, the mechanisms by which defective Rab7 leads to disease remain poorly understood. Results We used zebrafish to investigate the effects of CMT2b-associated Rab7 mutations in a vertebrate model. We generated transgenic animals expressing the CMT2b-associated mutant forms of Rab7 in sensory neurons, and show that these Rab7 variants cause neurodevelopmental defects, including defects in sensory axon growth, branching and pathfinding at early developmental stages. We also find reduced axon growth and branching in neurons expressing a constitutively active form of Rab7, suggesting these defects may be caused by Rab7 gain-of-function. Further, we use high-speed, high-resolution imaging of endosome transport in vivo and find that CMT2b-associated Rab7 variants cause reduced vesicle speeds, suggesting altered transport may underlie axon development defects. Conclusions Our data provide new insight into how disease-associated alterations in Rab7 protein disrupt cellular function in vertebrate sensory neurons. Moreover, our findings suggest that defects in axon development may be a previously unrecognized component of CMT2b disease.